Investigating Self-efficacy Levels Among The Teaching Staff Members At The Faculty Of Arts And Languages At Laghouat University - Guelila ,Salima; Kaddouri ,Elhadj (University of Eloued جامعة الوادي, 2024)
Abstract: The present study aims to investigate the level of self-efficacy among faculty members at the College of Arts and Languages, University of Laghouat. In pursuit of this goal, rigorous descriptive data collection methods were employed to ensure accuracy and reliability in the findings. Additionally, thorough validation procedures were implemented to ensure the reliability and validity of the Self-Efficacy Scale developed by Wala Yousef (2016) for data collection. After confirming the psychometric properties and their application to a sample of 80 male and female teachers, statistical analysis revealed several key findings. The study found a high level of self-efficacy among participants, and no statistically significant differences in its levels were attributed to gender or specialization.
Keywords: Self-efficacy; Performance; Teaching staff member.